AN EMPIRICAL ANALYSIS OF DAILY INTERNATIONAL TOURIST ARRIVALS AND RISK BY LAND TRANSPORT: A CASE OF THE ASIA HIGHWAY IN SONGKHLA PROVINCE OF THAILAND - HARI SHARMA NEUPANE (Centre For Tourism Planning and Development, 2013)
Asian Highway route No. 4, the only main national highway that links to the North South Economic corridor of the Greater Mekong Sub-region at Bangkok, is the gateway for East Asian countries to enter into the Thailand by land transport. Hence, the twin purposes of this paper are to a) appraise the present state of international tourist arrivals by land transport into Songkhla province of Thailand and to b) model the associated risk. Conditional mean and conditional volatility models from the ARCH family were adopted to illustrate the behavior of daily international tourist arrivals into the province. The parameters of the conditional mean and conditional volatility models are statistically significant and the Quasi Maximum Likelihood estimators are also valid and statistically consistent. The results show that almost 80% of those arrivals were from Malaysia and that short run risk is persistent. Negative asymmetric behavior is also observed in the daily international arrivals by land. The strategic implications of this empirical study envisage sufficient room for intervening or amending provincial tourism policy to better attract and stabilize Malaysian tourist arrivals and to promote tourism as a local business.